Genetic characterization of commercial Saccharomyces cerevisiae isolates recovered from vineyard environments using comparative genome hybridization on array (aCGH) - Duarte, Ricardo Franco (2011)
The use of commercial S. cerevisiae wine strains as fermentation starters has been extensively generalized over the past two decades. Within our previous work we showed that such strains are disseminated from the winery and their permanence in nature induced genetic changes in comparison to the commercial “mother” strain. The objective of the present study was to evaluate genome variations among four isolates of the commercial strain Zymaflore VL1 that were re-isolated from vineyards close the wineries, in comparison to the commercial “mother” strain by the use of comparative genome hybridization on array (aCGH). Hierarchical cluster analysis showed some genome variability between both groups. Using one-way ANOVA we identified more than 50 genes with significant differences. Multi-class significance analysis revealed a group of 130 genes with reduced fold changes in the recovered strains, being the most relevant the PAU family, involved in the adaptation of yeast cells to stress during alcoholic fermentations. Our studies showed that genetic changes occur among isogenic strains of the commercial yeast Zymaflore VL1 that were re-isolated from environments. The depletion of several genes may reflect adaptive mechanisms that strains undergo as response to the conditions of vineyards that are very distinct from must fermentation environments.